2013
DOI: 10.1088/0004-637x/770/1/12
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Numerical Resolution on Coronal Density in Hydrodynamic Models of Impulsive Heating

Abstract: The effect of the numerical spatial resolution in models of the solar corona and corona/chromosphere interface is examined for impulsive heating over a range of magnitudes using one-dimensional hydrodynamic simulations. It is demonstrated that the principal effect of inadequate resolution is on the coronal density. An underresolved loop typically has a peak density of at least a factor of two lower than a resolved loop subject to the same heating, with larger discrepancies in the decay phase. The temperature f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 33 publications
9
127
0
Order By: Relevance
“…The uniformly high resolution along the z direction allows us to accurately describe both the steep transition region and the moving shock front. To determine that the resolution in the steep gradient regions was high enough (e.g., Bradshaw & Cargill 2013), we made a test at higher spatial resolution along z (dz = 0.5 × 10 6 cm) and ascertained that the results do not change except for a few details.…”
Section: Loop Setupmentioning
confidence: 99%
“…The uniformly high resolution along the z direction allows us to accurately describe both the steep transition region and the moving shock front. To determine that the resolution in the steep gradient regions was high enough (e.g., Bradshaw & Cargill 2013), we made a test at higher spatial resolution along z (dz = 0.5 × 10 6 cm) and ascertained that the results do not change except for a few details.…”
Section: Loop Setupmentioning
confidence: 99%
“…In this work, the resolution was such that the smallest grid cell width was 0.12 km. Bradshaw and Cargill (2013) and others found that an inadequate resolution of the transition region primarily leads to an underestimated coronal density.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The evolution of the impulsively heated loop was simulated using the 1D hydrodynamics and radiation code HYDRAD (Bradshaw andMason, 2003a, 2003b;Bradshaw and Cargill, 2013). The loop begins in an initial idealised equilibrium where the hydrostatic equations are solved from the footpoint to the loop apex for one side and mirrored on the basis of symmetry.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We approximated the observed structure as a long loop and modelled it using the 1-D hydrodynamics and radiation code HYDRAD (Bradshaw and Cargill, 2013). The simulations were carried out taking into account the 15 most abundant elements in the solar atmosphere; to begin with they were considered to be in equilibrium for calculating the initial state and then not in equilibrium for the ensuing simulations.…”
Section: Modellingmentioning
confidence: 99%